2019
DOI: 10.1007/s11150-019-09457-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental unemployment and child health in China

Abstract: This paper studies the causal effect of maternal and paternal unemployment on child health in China, analyzing panel data for the period 1997-2004, when the country underwent economic reforms leading to massive layoffs. Using a FE-IV strategy, we find that paternal unemployment reduces child health, while maternal unemployment has beneficial child health impacts. Analysis of channels shows that paternal and maternal unemployment have different effects on income, time use, and children's diets. Though many esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…Phooko [51] revealed that women or child caregivers in rural areas are not allowed to work, but they must take care of the household, while men go to urban areas to work. Unemployment affects the household income and purchasing power (food), which, in turn, influences the nutritional status of children [110].…”
Section: Household Unemploymentmentioning
confidence: 99%
“…Phooko [51] revealed that women or child caregivers in rural areas are not allowed to work, but they must take care of the household, while men go to urban areas to work. Unemployment affects the household income and purchasing power (food), which, in turn, influences the nutritional status of children [110].…”
Section: Household Unemploymentmentioning
confidence: 99%
“…Additionally, the findings of this study showed that there was an association between father's employment and reasons for vaccination delay. The father's unemployment status could affect the health of their children (Pieters & Rawlings, 2020) in that unemployed fathers were positively associated with sickness of their children as a reason for vaccination delay. This study result could be explained as those fathers could also be poorly educated with a low level of knowledge about vaccination timeliness and contraindications, in addition to the influence of vaccines in preventing diseases and promoting their children's health.…”
Section: Discussionmentioning
confidence: 99%
“…13,28 É notório que o desemprego parental pode influenciar na má nutrição dos filhos e no aumento da incidência de baixo peso por idade, um dos fatores determinantes da ocorrência de sintomas graves e mortalidade por escorpionismo em crianças. 28,29 A disposição ambiental de lixo domiciliar no município esteve relacionada com a ocorrência do escorpionismo. O acúmulo de lixo favorece o aparecimento de escorpiões, devido à disponibilidade de alimento e abrigo.…”
Section: Discussionunclassified